(untitled) (Canadian Medical Education Journal, 2019)
As Canada continues to grow in diversity, health care providers will be encouraged to become more aware of cultural differences and their impact on health (7-9). The adoption of cultural competence teaching within medical curriculum was an important step. However, this approach does not fully capture the complexity and dynamism inherent to culture, and fails to acknowledge the culture(s) of biomedicine we are situated in as care providers. Without recognizing the role of culture in biomedical practice, we cannot fully implement a patient-centered approach to care. Applying the concept of cultural humility and its critical self-reflection is an important next step towards meaningfully addressing culture within the clinic.